2012
DOI: 10.1016/j.cardfail.2012.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Testing for Dilated Cardiomyopathy in Clinical Practice

Abstract: Background Familial involvement is common in dilated cardiomyopathy (DCM) and >40 genes have been implicated in causing disease. However, the role of genetic testing in clinical practice is not well defined. We examined the experience of clinical genetic testing in a diverse DCM population to characterize the prevalence and predictors of gene mutations. Methods and Results We studied 264 unrelated adult and pediatric DCM index patients referred to 1 reference lab for clinical genetic testing. Up to 10 genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
119
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(129 citation statements)
references
References 32 publications
7
119
1
2
Order By: Relevance
“…Our previous analyses indicated that the overall detection rate for pathogenic DCM variants across all genes tested did not differ among age groups. 26 In our current data set, detection rates did not differ among age groups except for those for the two most recent gene panels (24 and 46 genes; Supplementary Figure S2 online). Here, the higher detection rate in the adult and pediatric groups was driven mostly by TTN and DSP, although it should be noted that the numbers behind some of these detection rates are small (for confidence intervals, see Supplementary Table S2 online).…”
Section: Clinical Sensitivitymentioning
confidence: 62%
See 1 more Smart Citation
“…Our previous analyses indicated that the overall detection rate for pathogenic DCM variants across all genes tested did not differ among age groups. 26 In our current data set, detection rates did not differ among age groups except for those for the two most recent gene panels (24 and 46 genes; Supplementary Figure S2 online). Here, the higher detection rate in the adult and pediatric groups was driven mostly by TTN and DSP, although it should be noted that the numbers behind some of these detection rates are small (for confidence intervals, see Supplementary Table S2 online).…”
Section: Clinical Sensitivitymentioning
confidence: 62%
“…Interestingly, the clinical sensitivity for individuals with a family history of DCM was similar to that obtained for the entire cohort (with positive rates improving from 6.9-8.6% to 31-38%) and is consistent with our previous, smaller study. 26 This is different from what has been reported for HCM, for which a family history substantially increases the likelihood of detecting a clinically relevant variant. A second variable that is often suspected to correlate with detection rates is age.…”
Section: Clinical Sensitivitymentioning
confidence: 67%
“…These studies suggest that mutations in sarcomeric genes, including TTN (titin), MYH7 (myosin heavy chain), TNNT2 (cardiac troponin T) and TPM1 (α-tropomyosin) are the most common etiologies, collectively accounting for ~30% of cases. 8,16,[21][22][23] Mutations in LMNA, which encodes Lamin A/C, a nuclear envelope protein, have been shown to cause different phenotypes associated with DCM, including DCM with limb-girdle or Emery-Dreifuss muscular dystrophy. Patients with LMNA mutations and DCM also have electrical instability (DCM+E), with supraventricular arrhythmias and atrioventricular block (AVB) often present before systolic dysfunction.…”
Section: Dcm Disease Genesmentioning
confidence: 99%
“…16 However, the likelihood of finding a mutation appears less likely in older patients (> 40 years) with non-familial disease. 23 Ordering providers should be aware of the limitations of genetic testing for DCM, especially as they apply to indeterminate and "negative" test results in index patients. Importantly, not all genetic variation identified by genetic testing is pathogenic, and clinical decisions should not be predicated on genetic variants of uncertain or indeterminate clinical significance.…”
Section: Genetic Testing and Family Evaluationsmentioning
confidence: 99%
“…For example, mutations in the myosin heavy chains, myosin-binding protein C, cardiac troponins and calcium handling protein genes are associated with more than one type of cardiomyopathy. DCM in particular, has been associated with a large number different genes [8]. Moreover, within the individual genes, multiple mutations and variants have been described and novel mutations private to individual families continue to be identified.…”
Section: Introductionmentioning
confidence: 99%